A symmetric image encryption algorithm based on mixed linear–nonlinear coupled map lattice - Zhang, Ying-Qian; Wang, Xing-Yuan (Information sciences, 2014)
We propose a new image encryption algorithm based on the spatiotemporal chaos of the mixed linear–nonlinear coupled map lattices. This spatiotemporal chaotic system has more outstanding cryptography features in dynamics than the logistic map or the system of coupled map lattices does. In the proposed image encryption, we employ the strategy of bit-level pixel permutation which enables the lower bit planes and higher bit planes of pixels permute mutually without any extra storage space. Simulations have been carried out and the results demonstrate the superior security and high efficiency of the proposed algorithm.